Synthesis, Antioxidant and Antimicrobial Activities of Schiff Bases derived from Aldehydes and Ketones - AL-Hussam, Aghadeer Abdulaziz; AL-Jaꞌady, Amat Mohammed; AL-Shamiri, Eshraq Habib; AL-Hussam, Ghaida Abdulghafoor; AL-Miklafi, Soha Ibrahim; AI-Zawqary, Zina Naji (University of Science and Technology, Sana’a, 2026)
In this project, the synthesis of 1,3‑thiazole (3) by diazotization of aniline and Azo-resacetophenone (2) and its coupling reaction with thiosemicarbazide, followed by condensation of the Piperonal give the substrate azo Schiff bases (4), which also obtained by the reaction of Piperonal with thiosemicarbazide to give compound (Z) followed by condensation with an Azo-resacetophenone (2) afforded the hydrazinyl-1,3-thiazoles (4). The prepared starting material was reacted with Resorcinol to give a Azo-resacetophenone (2), in high yield, and the later compound was treated with Sodium Azide NaN3, amino acid (glycine and alanine), Mercaptoacetic acid (thioglycolic acid), phthalic anhydride, 2-Aminobenzoic acid, hydroxyl acetic acid (Glycolic acid), Lactic acid to give the heterocyclic derivatives of Titrazoles (4a), imidazolidine-4-one (4b), (4c), 4-thiazolidinones (4d), 1,3-Oxazepine-4,7-dione (4e), Hydroquinazoline (4f), Oxazolidines (4g) and (4gg), respectively. 1,3-oxazepine-4,7-dione compounds (4e) have been reacted with phenyl hydrazine to produce 1,3-diazepine-4,7-dione compounds (4ee), also, 4-thiazolidinones (4d) have been reacted with p-dimethylaminobenzaldhyde to produce thiazolidinone ring (4dd). Synthesis of the designed compounds (1-4gg) has been successfully achieved. Purity and characterization of the synthesized compounds were confirmed by determination of physical properties (melting points & Rf values), and some of the prepared compounds have been characterized by FT-IR techniques. The final products were screened for their antibacterial and antioxidant activities. The synthesized derivatives were evaluated for their antibacterial activity against Gram-positive bacteria (Staphylococcus aureus, S. epidermidis and Strept. Pyogenes) and Gram-negative bacteria (Escherichia coli, K. pneumonia and Salmonella typhi), the results show that some of prepared compounds had inhibition activity against some types of bacteria, but, some of them gave synergistic activity with some of antibiotic, while other compounds didn't show any kind of used disease bacteria. The results showed significant activity against both types of bacteria. Compound (4c) were found to exhibit highest activity against S. aureus, compounds 3, 4, 4a and (4ee) give promising activity against S. aureus, while compounds (Z) and (4gg) give promising activity against S. epidermidis, and compound (4a) having specific strong effect against the Strept. Pyogenes bacteria with an IZ = 41 mm. Further structural modifications and screening is to be required to confirm the more and still better activity. Also, these compounds were exhibited higher antioxidant activity by given methods, in vitro antioxidant activity (IC50 values) of the synthesized compounds in comparison with the reference antioxidant BHA and ascorbic acid. The antioxidant activity of the most compounds were strongly compressed with ascorbic acid. The antioxidant activity of the synthesized compounds 2, 3a, 4b, 4d, 4dd, 4e, 4ee and 4g with IC50 value 22.383, 24.283, 15.496, 25.87, 16.51, 10.21, 38.57 and 18.407 μg/ml to possess very strong antioxidant activity better than another prepared compounds.